Optimal Labor-Market Policy in Recessions - Philip Jung; Keith Kuester (University of Mannheim, Department of Economics, 2011)
We examine the optimal labor market-policy mix over the business cycle. In a search and matching model with risk-averse workers, endogenous hiring and separation, and unobservable search effort we first show how to decentralize the constrained-efficient allocation. This can be achieved by a combination of a production tax and three labor-market policy instruments, namely, a vacancy subsidy, a layoff tax and unemployment benefits. We derive analytical expressions for the optimal setting of each of these for the steady state and for the business cycle. Our propositions suggest that hiring subsidies, layoff taxes and the replacement rate of unemployment insurance should all rise in recessions. We find this confirmed in a calibration targeted to the U.S. economy.
urn:nbn:de:bsz:180-madoc-296303
Keywords: E32; E24; J64; 330; unemployment; search and matching; endogenous separations